Ответы и объяснения

2013-02-05T05:07:44+00:00

(3-x)^3+17=-10+x^2(9-x)

3^3-3*3^2x+3*3x^2-x^3+17=-10+9x^2-x^3

27-27x+9x^2-x^3+17+10-9x^2+x^3=0

54-27x=0

54=27x

x=2

2013-02-05T05:33:35+00:00

(3-Х)^3+17=-10+X^2(9-X)

9-3X+17=-10+18X-2X(в квадрате)

9-3X+17+10-18X+2X(в квадрате)=0

2X(в квадрате)-21X+36=0

a=2  b=-21  c =36

D=b(в квадрате)-4ac=-21(в квадрате)-4^36^2=441-288=153

 

X1,2=-b+-(квадратный корень из числа 153)/2a

 

X1=(21+(квадратный корень из   153))/2^2=(21+(квадратный корень из  153))/4        

X2=(21-(квадратный корень из 153))/2^2=(21-(квадратный корень из  153))/4        

Ответ:X1=(21+(квадратный корень из 153))/4 Х2=(21-(квадратный корень из 153))/4